2013
DOI: 10.1002/psp.1759
|View full text |Cite
|
Sign up to set email alerts
|

Self‐employment, Internal Migration and Place Embeddedness

Abstract: Little is known about the individual location behaviour of self‐employed entrepreneurs. Population geography has not researched this issue and entrepreneurship literature has given it little attention. This paper examines whether self‐employed entrepreneurs are ‘rooted’ in place and also whether those who are more rooted in place are more likely to enter self‐employment, thereby shedding new light onto the place embeddedness of self‐employment. Drawing on data from the German Socio‐Economic Panel Study (SOEP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…We thus propose that firm relocation processes and migration of business owners can be intimately linked. Existing work on both firm relocation and migration has not extensively addressed their reciprocal roles as the two literatures have developed largely in isolation (Reuschke, 2014). In this study, we take migration of business owners as the starting point as we are interested in the characteristics of moving business owners and how moving affects firm performance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus propose that firm relocation processes and migration of business owners can be intimately linked. Existing work on both firm relocation and migration has not extensively addressed their reciprocal roles as the two literatures have developed largely in isolation (Reuschke, 2014). In this study, we take migration of business owners as the starting point as we are interested in the characteristics of moving business owners and how moving affects firm performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With its focus on migration of the business owners, this study is one of the first to acknowledge the possible relationship between personal considerations of the business owner and consequent migration decisions and firm-level relocation patterns. Particularly given the fact that most firms are smalland increasingly sopersonal locational preferences of the owner and, if present, the partner may be salient factors in determining the preferred business location (Koster & Venhorst, 2014;Reuschke, 2014;Stam, 2007). Such factors may include access to alternative labour market opportunities and residential preferences that are based on access to certain amenities.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also found a positive association of self-employment and moves which could mean that there is a connection between house sales and running one's own business (REUSCHKE, 2013;BÖHEIM and TAYLOR, 1999;FIELDING 1992).…”
Section: Housing and The Economymentioning
confidence: 99%
“…Individuals often have histories of spatial relocation in their pre-entry careers through which they accumulate the experience and knowledge necessary to start a firm (Harrison et al 2004;Reuschke 2014). Knowledge acquisition across different geographical settings may turn these individuals into the most promising entrepreneurs (Dahl and Sorenson 2012;Frederiksen et al 2016).…”
Section: Introductionmentioning
confidence: 99%